Awareness about diabetes mellitus and DKA among medical students: an observational study - G., Manu; M., Narasimhamurthy K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Diabetes Mellitus (DM) is a global epidemic and a leading cause for increased mortality and morbidity. The prevalence of Diabetes is very high so the management of DM and its complication like diabetic ketoacidosis (DKA) is very crucial in today’s world. Medical students being the future pillars of our health care system were included in this study to know their knowledge towards diabetes and its acute complication DKA. Methods: This study was a questionnaire based observational study conducted in Adichunchanagiri Institute of Medical Sciences, B G Nagara. Final year medical students and interns were included in the study. Results: A total of 150 (75 from each group) questionnaires were collected and analysed. Most of the final year students and interns were aware about the classical symptoms of diabetes (73.33% and 84% respectively) and were aware about the endocrine gland related to diabetes (82.6% and 94.6% respectively) however there were differences about the meaning of PPBS among both the groups. Interns (76%) had better knowledge regarding the fluid replacement in the management of DKA in compared to final year students (41.33%). There was statistically significant difference in knowledge between the two groups regarding GDM. Conclusions: This study identifies that both final year students and interns need to improve the practical knowledge towards diagnostic parameters of DM and treatment of DKA. Continous medical education programmes and workshops should be organised to enhance the knowledge towards DM and its complications.